2022
DOI: 10.3390/microorganisms10061078
|View full text |Cite
|
Sign up to set email alerts
|

DNA Markers for Detection and Genotyping of Xanthomonas euroxanthea

Abstract: Xanthomonas euroxanthea is a bacterial species encompassing both pathogenic and non-pathogenic strains and is frequently found colonizing the same host plants as X. arboricola. This presents the need to develop a detection and genotyping assay able to track these bacteria in microbial consortia with other xanthomonads. Eight X. euroxanthea-specific DNA markers (XEA1-XEA8) were selected by comparative genomics and validated in silico regarding their specificity and consistency using BLASTn, synteny analysis, CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…‘EuroXanth’ COST Action has seen its name immortalised after a new pathogen affecting walnut production was named after it, called Xanthomonas euroxanthea . Silva et al [ 2 ] developed DNA markers for the molecular detection of this new pathogen. Of the eight markers identified, the authors found that four were located in highly syntenic regions across eleven X .…”
Section: Integrating Science On Xanthomonas and ...mentioning
confidence: 99%
“…‘EuroXanth’ COST Action has seen its name immortalised after a new pathogen affecting walnut production was named after it, called Xanthomonas euroxanthea . Silva et al [ 2 ] developed DNA markers for the molecular detection of this new pathogen. Of the eight markers identified, the authors found that four were located in highly syntenic regions across eleven X .…”
Section: Integrating Science On Xanthomonas and ...mentioning
confidence: 99%